Isolation of lactic acid bacteria (LAB) from mimosa pudica (Semalu) for production of bacterial cellulose - Lim, Bei Min; Junaidi, Zakaria; Siti Hatijah, Mortan; Shahril, Mohamad; Mohd Hairul, Ab. Rahim (Malaysian Society of Applied Biology, 2023)
Bacterial cellulose (BC) is a potential eco-friendly biopolymer. BC has higher crystallinity and purity compared to plant cellulose. Scientific studies on the production of BC from lactic acid bacteria (LAB) are minimal compared to other common bacteria such as Acetobacter xylinum. LAB was screened and isolated from different tissues of Mimosa pudica (medicinal plant) using MRS broth and agar as the selective medium. LAB isolates were subjected to 16S rRNA gene sequencing of all the bacterial isolates. BC was produced from all LAB isolates by incubating at 30 °C for 14 days in herbal tea medium (Strobilanthes crispus) and HS medium (control) with 130 r.p.m agitation. BC produced by two selected bacterial isolates was characterized using FESEM, FTIR, XRD, and TGA. Molecular analysis of the 16S rRNA gene of all the potential LAB isolates shows 99.86 - 100% identity to 16S rRNA sequences of other Lactobacillus plantarum strains. Two selected L. plantarum strains (LBM001 & LBM004) produce BC in sphere-like particles with a 1.4 to 2.2 µm diameter range of microfiber. FTIR analysis shows that BC produced by LBM001 and LBM004 have four similar cellulose regions identified in cellulose from other sources, which are O-H stretch (3400-330 cm-1), C-H stretch (2970-2800 cm-1), O-H bending (1620cm-1) and C-O-C stretch (1100-1073 cm-1). XRD analysis shows BC produced by the L. plantarum strains consists of two different XRD peaks at the 2θ angle of 21.53° and 21.85° instead of a single peak (22.76°) identified in the BC produced by A. xylinum and plant cellulose. A similar TG and DTG curved pattern was detected in the BC produced by the L. plantarum strains with the BC produced by A. xylinum and plant cellulose. The LAB isolates from M. pudica have potential in BC production based on the multiple characterization studies.